“Fools rush in”: Writing a history of the concentration camps of the South African War (Historia, 2021)
A recent article in the South African Journal of Science (SAJS) has created a certain amount of anger in Afrikaner circles after Rapport newspaper published a piece on it. This was followed by a discussion by Professor Fransjohan Pretorius, in a critique entitled "Toiletpraatjies Stink". His comments bring to the fore some of the very real problems in writing a history of the camps.
Keywords: South African War; Anglo-Boer War; concentration camps; poor whites; middle class culture; sanitation; hygiene; British Blue Books; Ladies Commission